The experimental study of energy dissipation during fatigue crack propagation under biaxial loading - Oleg Plekhov; Aleksei Vshivkov; Anastasia Iziumova; Aleksandr Zakharov; Valery Shlyannikov (Fracture and Structural Integrity)
The work is devoted to experimental study of heat flux evolution at the fatigue crack tip during biaxial loading with a goal to relate the heat flux to the rate of crack propagation under different loading conditions. The plane samples of titanium alloy (Grade 2) 1 mm thick were weakened by notch to initiate fatigue crack at their centers. Infrared thermography and the contact heat flux sensor, which is based on the Seebeck effect, were used to monitor the dissipated thermal energy. The samples were subject to cyclic loading with constant stress amplitude at different biaxial coefficients. The experimental results confirmed the previous conclusions of the authors about two regime of energy dissipation at fatigue crack tip under Paris regime. At the first stage, the power of heat flux is proportional to the product of the crack rate by the crack length. The second stage is characterized by a traditional linear relationship between the crack rate and the heat flux.